Welten Suriname : from love to serious business - Kryklii, Ganna (SAGE Knowledge. Cases., 2013)
Cees Welten, after starting his career at financial institutes, soon felt an inner drive to establish his own company, Welten, specializing in providing both education and secondment services for banks and insurance companies. Even though few companies could successfully compete with Welten in the Netherlands, Welten had difficulties in internationalization and many of its attempts failed. In 2012 Welten faced the burning issue of re-establishing its activities in Suriname. The company already had tried to expand in Suriname in 2008, but had been forced to withdraw for economic, political and cultural reasons.This case, introducing Cees Welten's dilemma on whether or not to return to Suriname, develops and highlights essential fields of an enterprise's internationalization process. The central issues entail how a company can select its foreign target market along with its entry mode; how it can assess its international marketability; what the steps are to prepare for implementing an internationalization strategy; how important the role of cultural differences is in internationalization; what is the role of the CEO in implementing internationalization; and how it is possible (if at all) to re-establish business in a foreign market after a failed attempt at internationalization.